Impact of website design features on experiential value and patronage intention toward online mass customization sites. Issue 2 (24th July 2020) - Zhang, Ying; Fiore, Ann Marie; Zhang, Ling; Liu, Xiaogang
Abstract : Purpose: To examine the relationships among website design features, consumer experience responses and patronage intention toward online mass customization (OMC) apparel websites. Design/methodology/approach: A total of 312 useable online surveys were obtained from Mainland China consumers. Multi-item scales were adopted to measure eight constructs: visual design; information quality; entertainment, aesthetic, educational, escapist experiences; flow; and patronage intention. Structural equation modeling (SEM) was conducted to determine factor structures and to test the hypothesized relationships among website design features, 4Es (entertainment, aesthetic, educational and escapist experiences), flow and consequent purchase intention toward OMC apparel websites. Findings: All hypotheses, but one, were supported. OMC website visual design; information quality; and entertainment, aesthetic and educational experiences had a positive effect on consumer patronage intention. Research limitations/implications: Limitations include using a sample of consumers from major cities in China; results cannot be generalized to all Chinese consumers. Websites were not actively navigated. Additionally, the present study examined only two dimensions of OMC website quality, visual design and information quality; more tangible and specific features could be considered in future research. Practical implications: The findings provide website designers and marketers with insights into experiences that may lead to an increase in patronage intention toward OMC websites. Originality/value: The study provides evidence that flow helps explain the impact of experiential value (i.e. 4Es) from website design features on patronage intention.